Biochemical study of zygotic embryogenesis in stone pine (Pinus pinea L.) and its potential contribution to the development of somatic embryogenesis protocols - Silva, A (2012)
In this work we followed the biochemical events that take place during developmental stages of zygotic embryogenesis in stone pine. It’s a totally new approach, since until now; the research was focused only on the biochemistry of the mature pine nuts (nutritional aspect). To study the biochemical changes that take place in zygotic embryogenesis, the female cone collections were made from June to September, 2007. The female cones collected over this period were from just a few weeks after fertilization through to complete embryo maturation. The morphological stages of the seed development were characterized and photographed at each date for further use in correlations between biochemical variation and embryo development. The increase in the fresh weight of the pine seeds from consecutive collections was approximately 1 mg per day. During this period, the water content decreased and an increase in organic matter was observed, indicating changes in the constituent components during the maturation process. In mature seeds, oil content was 33.26% and proteins represented 24.31%. The soluble and insoluble proteins were extracted acording to Brownfield et al. (2007) and analysed by SDS-PAGE. Results showed that soluble and insoluble proteins profiles varied in different phases of embryo maturation. Inorganic composition was also monitored at each collection date. A complete description of mineral elements variation includes Ca, Mg, K, P, Mn, Fe, Na, Zn and Cu. Ca, Mg and K were the predominat elements present in the mature seeds. A better understanding of biochemistry of zygotic embryogenesis in Pinus pinea L. could be relevant, and lead to complete plant propagation through SE. It is anticipated, for example, that the results of this work could contribute to the development of new culture medium formulation that might enhance the efficiency of stages of stone pine SE.